Source Code and Formal Analysis: A Reading of Passage - Willumsen, Ea (Transactions of the Digital Games Research Association, 2017)
Analysis of the source code of video games is not an integrated part of the formal analysis. Rather, few scholars have investigated how an analysis of the source code can inform a hermeneutic reading of the game. In this paper I will present a reading of the source code of Passage (Rohrer, 2007), argue for why a traditional focus on authorial intention is unnecessary when investigating the symbolism and metaphors of a game, and illustrate how source code analysis can inform the formal analysis of the executed game. Finally, I shall discuss how the source code relates to the game as a ‘work’, and how it can be used for studies of symbolism and metaphors. Thus, I will conclude that it is indeed a valuable method for game studies, although further studies should expand on the textual relation between executed game and source code.